2015
DOI: 10.1083/jcb.201505118
|View full text |Cite
|
Sign up to set email alerts
|

ATP8B1-mediated spatial organization of Cdc42 signaling maintains singularity during enterocyte polarization

Abstract: The disease-associated phospholipid flippase ATP8B1 decreases Cdc42 mobility at the apical membrane to ensure the formation of a single apical domain and to maintain healthy lumen architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Indeed, proper activation and recruitment of Cdc42 to the plasma membrane requires the oscillation of local PS concentration, which can be regulated by PE-flippase activity; that is, an increase in PE-flipping activity decreases the local PS concentration on the plasma membrane (Das et al, 2012;Saito et al, 2007). Similarly, ATP8B1 is required for the polarized localization of Cdc42 in mammalian cells (Bruurs et al, 2015). Because ATP8B1 is a PC flippase (Takatsu et al, 2014), the oscillation of local PS concentration can be regulated by PC-flippase activity of ATP8B1 to allow the proper activation and local clustering of Cdc42 at the apical membranes (Bruurs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, proper activation and recruitment of Cdc42 to the plasma membrane requires the oscillation of local PS concentration, which can be regulated by PE-flippase activity; that is, an increase in PE-flipping activity decreases the local PS concentration on the plasma membrane (Das et al, 2012;Saito et al, 2007). Similarly, ATP8B1 is required for the polarized localization of Cdc42 in mammalian cells (Bruurs et al, 2015). Because ATP8B1 is a PC flippase (Takatsu et al, 2014), the oscillation of local PS concentration can be regulated by PC-flippase activity of ATP8B1 to allow the proper activation and local clustering of Cdc42 at the apical membranes (Bruurs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that these Cdc42 knockout cells retain the ability to form a brush border but are nonetheless unable to ensure that polarization is restricted to a single site (3). We find that the singularity defect in the W4:NEC cells is rescued by reintroduction of wild-type Cdc42, demonstrating that yellow fluorescent protein (YFP)-tagged Cdc42 is still functional (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a nonsense mutation in the Atp11c gene was identified in UPS-1 cells (70). Several lines of evidence suggest that ATP8B1 translocates PS in bile canaliculi and apical membranes (72,74,75). In another study, RNA interference-mediated depletion of ATP8B1 did not affect translocation of PS in Caco-2 cells (76).…”
Section: Lipid Transport By P4-atpasesmentioning
confidence: 99%